Cultural distance, institutional distance and international trade - Sjoerd Beugelsdijk; Henri De Groot; Gert-Jan Linders; Arjen Slangen (European Regional Science Association (ERSA), 2004)
There is large variation in trade patterns across the world. Despite the popular discussion on the `death of distance', distance is still the most important variable explaining this variation. In explaining trade patterns across the worls, it is important to acknowledge the multiple dimensions of distance. In this paper, we empirically investigate the relevance of several of these dimensions. Apart from physical distance, we also consider the effects of cultural distance and institutional distance. Our results reveal the importance of all three dimensions. JEL classification: F14 Keywords: bilateral trade, gravity models, cultural distance, institutional distance
Keywords: F14; 330; bilateral trade; gravity models; cultural distance; institutional distance